Fish protein concentrate for human consumption: a review of its preparation by solvent extraction methods and potential for food applications - Kumoro, Andri Cahyo; Dyah Hesti Wardhani; Kusworo, Tutuk Djoko; Mohammad Djaeni; Tan, Chin Ping; Azis, Yusuf Ma'rifat Fajar (Faculty of Agriculture, Ain Shams University, 2022)
Fish protein concentrate (FPC) is prepared to recover valuable nutrients from fish flesh as an affordable, acceptable, and excellent protein source. This paper reviews the existing FPC preparation processes through solvent extraction. The influential operating parameters should be selected to obtain the highest FPC yield with superior functional properties. Furthermore, this paper also aims to review the functional properties and potential applications of the FPC for human consumption, i.e., food, beverage, cosmetics, and personal care. Clear FPC information summarized in this paper is expected to strengthen consumer understanding, motivate FPC manufacturers, and extend FPC utilization in any possible field.